2021
DOI: 10.1155/2021/8323661
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanism of Action of Salvia miltiorrhiza for the Treatment of Acute Pancreatitis Based on Network Pharmacology and Molecular Docking Technology

Abstract: Using network pharmacology and molecular docking, this study investigated the molecular mechanisms by which the active components in Salvia miltiorrhiza can alleviate acute pancreatitis. Initially, the active components of Salvia miltiorrhiza and the targets collected from the GeneCards database were screened based on the platform of systematic pharmacology analysis of traditional Chinese medicine. Subsequently, the active components were intersected with the disease targets. Also, interactions among the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…NCOA1, ESR1, and ESR2 are enriched in the estrogen signaling pathway. Studies have shown that NCOA1 is involved in the acute inflammatory process of AP through the regulation of IL-17 [ 60 ]. Both ESR1 and ESR2 can mediate anti-inflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…NCOA1, ESR1, and ESR2 are enriched in the estrogen signaling pathway. Studies have shown that NCOA1 is involved in the acute inflammatory process of AP through the regulation of IL-17 [ 60 ]. Both ESR1 and ESR2 can mediate anti-inflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking technology docks known small-molecule active substances with related target proteins, which can clarify the mechanism of action between active TCM ingredients and targets at the molecular level [ 43 , 44 ]. At present, molecular docking technology plays an important role in elucidating the mechanism of action between active ingredients of TCM [ 45 , 46 ] and related target proteins in many diseases, such as cardiovascular disease [ 25 ] and cancer [ 26 ]. Therefore, we conducted preliminary screening with reference to the five principles of drug-like standards and other screening conditions of “drug similarity” and obtained 22 compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Genes. Finally, KEGG functional enrichment analysis was performed on these target genes [59]. Te reliability of the predictions was further assessed to know whether enriched pathways were classical and critical pathways in unstable angina.…”
Section: Validation Of the Function Of Targetmentioning
confidence: 99%